A Trial Implementation of Using Deuterium Oxide Dose-to-Mother and Dilution Technique Among Beninese Children: Challenge and Critical Points - LOKONON, Jaurès Hontongnon Félix; AMOUSSA HOUNKPATIN, WALIOU BODOURIN AYANDA; DIOUF, Adama; FLENON, Aubierge Joelle; SONON, Félix Bodjrenou; KAYODE, pOLYCARPE Pierre Adéchola; IDOHOU DOSSOU, Nicole (My University, 2019)
Within decade years, the deuterium dilution techniques are largely used in developing countries for breast milk output and body composition which are the important indicators of public health nutrition interventions. But the implementation of these techniques needs a familiarity with standard operating procedures. This paper presented the challenge met while using these stable isotope methods among Beninese children. The checking data and estimate of deuterium equilibration period were tested on 15 children aged 6-22 months for the body composition (BC) and 08 mother-child pairs having 5.5 months children aged for assessing breast milk intake (BMI). We have found that collecting saliva from 6 months children was very demanding. Children above 6 months aged chewed up the dentals swabs or cotton wool. Instead of cotton stalk, mother’s index finger has been used to overcome saliva collection challenge. For BC measurement, some mothers got angry and left before the third saliva collection. Seven children have rejected the dose or vomited immediately after the dose administration. The plateau equilibration was between 2 and 3 hours. Concerning data quality, the Total Body Water percentage at 2, 2.5 and 3 hours were between 40-75% for 7 children. Only one over 8 children was less than 60mg/kg of total error for BMI output. These results are crucial to conduct the large study. It showed precautions that might be taken into account in order assure high quality data about BMI output and children BC and therefore to improve the quality of the assessment public health actions.
Keywords: Deuterium Oxide; Fat Free Mass; Fat Mass; Breastmilk